2021
DOI: 10.21203/rs.3.rs-316386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improvement of the optical and photocatalytic properties of ZnAl2O4: 1% La3+, x% Pb2+ nanoparticles synthesized by citrate sol-gel route

Abstract: Samples of pure zinc aluminate (ZnAl2O4) and doped both with lead (Pb2+) at different ratios (0, 0.5, 1, 1.5, 2 and 2.5% mol) and a constant amount of lanthanum (La: 1% mol), were prepared by the citrate sol-gel technique, and then annealed at 900°C for 2h. In order to study the structural, optical and thermal properties; different characterization methods were used, such as: powder X-ray diffraction (XRD), scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDX), differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…A small peak around 815 cm −1 and 808 cm −1 is related to vibrations modes of Al 3+ ion occupied at tetrahedral sites [10]. The band lies between 450 and 700 cm −1 certify the formation of the cubic structure of ZnAl 2 O 4 which is analogous to the XRD results [12]. The sharp peak at 681 cm −1 may correspond to the Al-O stretching type mode of vibrations in a tetrahedral coordination [16].…”
Section: Ftir Analysissupporting
confidence: 68%
See 3 more Smart Citations
“…A small peak around 815 cm −1 and 808 cm −1 is related to vibrations modes of Al 3+ ion occupied at tetrahedral sites [10]. The band lies between 450 and 700 cm −1 certify the formation of the cubic structure of ZnAl 2 O 4 which is analogous to the XRD results [12]. The sharp peak at 681 cm −1 may correspond to the Al-O stretching type mode of vibrations in a tetrahedral coordination [16].…”
Section: Ftir Analysissupporting
confidence: 68%
“…It may be due to the formation of impurities phase during their sample synthesis. Filali et al [12] noticed a similar band gap energy in transition metal ion (Pb 2+ ) doped ZnAl 2 O 4 samples and the absorption edge shift towards large wavelength with reported that increase in dopants concentration. Radha et al [17] reported the detailed characterization of Zn 1-x Cu x Al 2 O 4 (0.0 x 0.1) samples after synthesis by hydrothermal method.…”
Section: Uv-vis Spectroscopymentioning
confidence: 70%
See 2 more Smart Citations